2017
DOI: 10.3892/etm.2017.5665
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNA-539 and osteopontin in rheumatoid arthritis

Abstract: Abstract. The present study aimed to investigate the role and mechanism of microRNA-539 (miR-539) in rheumatoid arthritis (RA). A total of 68 RA patients and 46 osteoarthritis patients were enrolled into the current study. Peripheral blood and joint fluid were collected prior to treatment. Reverse transcription-quantitative polymerase chain reaction was performed to detect osteopontin (OPN) mRNA and miR-539 expression levels, while ELISA and western blot analysis were applied to detect OPN protein expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…These molecules inhibit the translation of mRNA by targeting the binding sites at the 3'-untranslated region (UTR) of mRNA ( 11 ). miR-let-7a ( 11 ) and miR-539( 12 ) are reported to regulate the expression of SPP1. Bioinformatics prediction suggests that miR-433 (accession no.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules inhibit the translation of mRNA by targeting the binding sites at the 3'-untranslated region (UTR) of mRNA ( 11 ). miR-let-7a ( 11 ) and miR-539( 12 ) are reported to regulate the expression of SPP1. Bioinformatics prediction suggests that miR-433 (accession no.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported that miR-539-5p suppressed tumor cell migration and invasion [28,29], promoted the development and progression of rheumatoid arthritis [30], as well as regulated osteoblast proliferation and differentiation and osteoclast apoptosis [31]. However, the role of miR-539-5p in the migration of rMSCs is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…U6 was used as a reference gene for miR-155 and GAPDH was used as a reference for all other genes. The 2 -ΔΔCq method was used to calculate quantitative gene expression (15).…”
Section: Methodsmentioning
confidence: 99%